Pandemic-related mental health risk among front line personnel. (May 2021) - Wright, Hannah M.; Griffin, Brandon J.; Shoji, Kotaro; Love, Tiffany M.; Langenecker, Scott A.; Benight, Charles C.; Smith, Andrew J.
Abstract: The mental health of frontline workers is critical to a community's ability to manage crises and disasters. This study assessed risks for mental health problems (traumatic stress, depression, anxiety, alcohol use, insomnia) in association with pandemic-related stressors in a sample of emergency and hospital personnel ( N = 571). Respondents completed self-report surveys online from April 1st to May 7th, 2020 in the Rocky Mountain region of the United States. Results showed that roughly fifteen to thirty percent of respondents screened positive for each disorder. Odds of screening positive were similar between groups for probable acute traumatic stress, depressive disorder, anxiety disorder, and alcohol use disorder; emergency personnel reported significantly higher rates of insufficient sleep than healthcare workers. Logistic regressions showed that respondents who reported having an immunocompromised condition had higher odds of acute traumatic stress, anxiety, and depression. Having an immunocompromised household member was associated with higher odds of insufficient sleep and anxiety. Being in a direct care provision role was associated with higher odds of screening positive for risky alcohol use. Being in a management role over direct care providers was associated with higher odds of screening positive for anxiety, risky alcohol use, and insufficient sleep. There was an inverse relationship between number of positive COVID-19 cases and anxiety, such that as positive cases went up, anxiety decreased. Overall, the mental health risks that we observed early in the COVID-19 pandemic are elevated above previous viral outbreaks (SARS) and comparable to rates shown in disasters (9/11 attacks; Hurricane Katrina).